TIMBER BEAM REPAIR BASED ON POLYMER-CEMENTITIOUS BLENDS - André L. Christoforo; Tulio H. Panzera; Victor A. de Araujo; Juliano Fiorelli; Francisco A. R. Lahr (Engenharia Agrícola, 2017)
ABSTRACT This study aims to manufacture and apply polymer-cementitious blends based on a combination of epoxy polymer and Ordinary Portland Cement (OPC) for timber beam repair. The material was used to repair timber beams of “Maçaranduba” (Manilkara sp.) and “Cedro doce” (Cedrella spp) wood species. A full factorial design was conducted to investigate the effect of cement particle content (0wt%, 30wt%, 40wt% and 50wt %), type of cement (ASTM-II and ASTM-III), and pigment addition (0wt% and 0.2wt%) on the physical and mechanical properties of the blend. The cement content factor affected all properties investigated. The highest elastic modulus was achieved by the blends produced with 50wt% of cement and 0.2wt% of pigment inclusion. This condition was used to repair the timber beams evaluated under four-point bending test. The insertion of the blends in timber beams achieved superior load levels to the unreinforced woods in both species, inferior load levels to the reference condition (without defects) in “Cedro doce”, and superior to the reference condition in “Maçaranduba”. These results were justified by the low density of “Cedro doce”, providing a better blend-wood interface adhesion.